A new cave-dwelling Centromerus from Sardinia (Araneae: Linyphiidae) - Bosmans, Robert; Gasparo, Fulvio (Fragmenta entomologica, 2014)
Centromerus marciai sp. n. is described on both sexes on specimens collected in a karstic cave in the province of Nuoro, North-eastern Sardinia, Italy. Differences with other species of the genus Centromerus Dahl, 1886 occurring in Sardinia are pointed out.